2015
DOI: 10.1080/13504509.2015.1111269
|View full text |Cite
|
Sign up to set email alerts
|

The victims of unsustainability: a challenge to sustainable development goals

Abstract: Environmental unsustainability is due to both structural features and historically specific characteristics of industrial capitalism resulting in specific patterns of production and consumption, as well as population growth. Sustainability literature criticises the established corporate and political power hegemonies, interested in maintaining economic growth, as well as inability or unwillingness of citizen-consumers to counteract these hegemonic tendencies. Yet, official policies are still targeted at social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(105 citation statements)
references
References 23 publications
1
101
0
3
Order By: Relevance
“…After the review of 68 abstracts, 37 full articles were selected, and 12 of them were kept for analysis. Except for [22], no articles were found that related the SDGs explicitly to environmental ethics. The 12 selected articles exemplify interpretations within the environmental ethics framework rather than provide an overview of existing SDGs literature.…”
Section: Ethical Positioning Of Sdg Interpretationsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the review of 68 abstracts, 37 full articles were selected, and 12 of them were kept for analysis. Except for [22], no articles were found that related the SDGs explicitly to environmental ethics. The 12 selected articles exemplify interpretations within the environmental ethics framework rather than provide an overview of existing SDGs literature.…”
Section: Ethical Positioning Of Sdg Interpretationsmentioning
confidence: 99%
“…She discusses the role of neglected and disadvantaged stakeholders in the SDG debate, including nature as a "third party." Kopina's interpretation is highly normative, promoting for example anti-capitalist views to protect the "victims of unsustainability", advocating "an invocation of ethical duty toward environment and its elements" [22] or fronting a claim for unity: "[W]e have to be on the same page and speak of the same meaning. In a finite world, we need to accept once and for all that sustainability cannot be about further growth.…”
Section: Conclusion: Moderate Biocentrism and The Sdgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, assessing sustainability to ensure that Earth will be able to support its diverse life forms in the future has become critically important. Unsustainability may result from (over) emphasizing one dimension over the others (Klooster 2010;Villamagna et al 2013;Kopnina 2016) and thus, considering the 3D approach becomes essential. Some recent studies on the forest-based bioeconomy and its multidimensional impacts can be found for example in Heink andKowarik (2010), den Herder et al (2012), Leskinen et al (2012), Cambero and Sowlati (2014) and Jäppinen et al (2014).…”
Section: Defining and Assessing Sustainability Of Forestrymentioning
confidence: 99%
“…Sustainability has been approached from many angles, such as compensation, thresholds and strong or weak sustainability (see Ayres et al 2001;De Mare et al 2015;Janeiro and Patel 2015). The very concept of sustainability has also been criticized for its anthropocentricity (see Kopnina 2016). It is important to notice that the conditions in all the 3Ds do vary between locations -yet, some impacts have a global reach (i.e.…”
Section: Interlinked Dimensionsmentioning
confidence: 99%